Community Empowerment of Yellow Pumpkin Food Processing as an Alternative Snack to Prevent Diabetes Mellitus in The Community in Mangunharjo Tembalang Sub-District, Semarang City - Fatimah Fatimah; Nanang Sulaksono; Yeti Kartikasari; Veny Nur Aini; Dimas Prakoso; Siti Masrochah (Poltekkes Kemenkes Semarang, 2026)
Mangunharjo Village is expected to realize a healthy village and improve health through efforts to establish healthy SMEs in the village. Besides its high nutritional value, pumpkin is easy to find, grow, and is affordable. Therefore, it is suitable for use as a basic ingredient in making alternative snacks for people with diabetes. The method used in this activity is a training approach, followed by program implementation with mentoring until certification and licensing. Each stage will be evaluated to obtain feedback and further improvement efforts. The results and discussions from this activity showed participants' awareness and understanding of health and the importance of replacing their consumption with healthier ingredients. Participants were able to process and package processed pumpkin products properly. Furthermore, a booklet and video guide on product processing were developed. This activity concluded that it was successfully implemented. There was increased awareness among residents about the importance of maintaining blood sugar levels. Therefore, it is necessary to increase the motivation of the assisted villages to produce other healthy food and beverage products to improve health and increase their income.